Pengaruh Online Customer Review, Electronic Word Of Mouth, Dan Brand Image Terhadap Minat Beli Merchandise Lawless Jakarta (Studi Kasus Pada Mahasiswa Kota Malang) - Adrian Ferryawan Abel; Agus Widarko; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Buying interest is directly related to consumer feelings and sentiments, if a consumer feels happy and satisfied it means it can increase purchase interest, while if consumers feel dissatisfied when buying a product it will usually eliminate interest in buying. The purpose of this study is to determine the influence of online customer reviews, electronic word of mouth, and brand image on the interest in buying Lawless Jakarta merchandise. . Research methods using a quantitative approach and using primary data and secondary data. The sampling technique uses a non-probability sampling method with purposive sampling techniques. Determination of the number of samples using the Lemeshow formula which amounted to 96 respondents. Data collection method using google form questionnaire. The data analysis methods used are instrument tests, normality tests, classical assumption tests, multiple linear regression analysis and hypothesis tests using SPSS 25 software. The results showed that online customer reviews, electronic word of mouth, and brand image on the interest in buying Lawless Jakarta merchandise simultaneously and partially had a positive and significant effect. The influence of online customer reviews, electronic word of mouth, and brand image on the interest in buying Lawless Jakarta merchandise shows a coefficient of determination of 39.6%. Keywords: Online Customer Review, Electronic Word of Mouth, Brand Image, and Interest Buying.